ANALISIS BIBLIOMETRIC DALAM IMPLEMENTASI ERP SEBUAH ORGANISASI - Ernando, Ryan; Tisno Atmojo, Wahyu (STMIK Sinar Nusantara, 2024)
This research can be used to analyze research trends related to the implementation of Enterprise Resource Planning (ERP) systems through a bibliometric approach. ERP has become one of the most crucial management systems in improving the efficiency and integration of business processes in various industries. However, the success of ERP implementation often depends on many factors, such as organizational readiness, technical complexity, and change management. In this study, bibliometric data was collected from various databases to evaluate the development of research related to this topic. The analysis includes identifying the most publications, main keywords, author and country trends, and collaboration between researchers. The results of the analysis show a significant increase in the number of publications related to ERP implementation in the last five years, with a major focus on implementation success factors, the latest technologies used, and case studies from various industry sectors such as. This research has 5 stages, namely filtering search keywords, initial search resilt, refinement of search results, compile premilinery data statistics, data analysis. This research is expected to provide a more in-depth picture of academic developments related to implementation. ERP and provide insight for researchers and practitioners who are interested in this topic, ERP is still the main choice seen from its trend which has been 5 years in a row always going up. This research is very important for researchers who want to conduct research related to ERP to see the latest research trends.